(untitled) (Linguostylistic Studies, 2015)
The attempt to analyze of individual-author’s names of emotions and feelings with positive and negative connotation fixed in the Ukranian poetical texts of the last century is made. The most productive classes of parts of author’s lexical new-formations are reviewed, the main lexical and semantic groups of innovations are singled out, the semantic features of occasional color names’ emotives are analyzed. The author’s lexcal new-formations using with antonymic component are dicribed. It is marked their semantics to base on contextual polarity items that make up the nominations. The distinctive stylistic features of poetic texts are the active use of individual-author’s juxtaposition with both pre-positive and postpositive signivied components. Key words: author’s lexical new-formations, lexical innovation, occasional word, lexical and semantic group, feelings and emotions of a positive and negative response, semantics, lexeme, word compositions, Ukranian poetry of the 20th century. References